2014
DOI: 10.1021/nl500925n
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of a Graphene-Zinc Phosphide Solar Cell Using the Electric Field-Effect

Abstract: ABSTRACT:The optical transparency and high electron mobility of graphene make it an attractive material for photovoltaics. We present a field-effect solar cell using graphene to form a tunable junction barrier with an Earth-abundant and low cost zinc phosphide (Zn 3 P 2 ) thin-film light absorber. Adding a semitransparent top electrostatic gate allows for tuning of the graphene Fermi level and hence the energy barrier at the graphene-Zn 3 P 2 junction, going from an ohmic contact at negative gate voltages to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…[25][26][27][28][29] Distinct from traditional Schottky diode, the barrier height of graphene/semiconductor Schottky diode is tunable as the Fermi level of graphene and semiconductor can be adjusted independently benefiting from the nature of van der Waals contact, the low density of energy states near Dirac point and small screening length of graphene. [30,31] Although the tunable barrier height is the key to the physical picture of graphene/semiconductor Schottky diode, and structures with thin metal, ferroelectric polymer and ionic liquid as gating layer have been employed in graphene based electronic and optoelectronic devices [32][33][34][35][36][37][38][39][40], its applications in solar cell has not been explored systemically and the performance needs to further improved. Recently, Vazquez-Mena et al reported thin Au layer gated graphene/zinc phosphide solar cell with power conversion efficiency (PCE) of 1.9%, which is still low considering the relatively large band gap of zinc phosphide of 1.5 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29] Distinct from traditional Schottky diode, the barrier height of graphene/semiconductor Schottky diode is tunable as the Fermi level of graphene and semiconductor can be adjusted independently benefiting from the nature of van der Waals contact, the low density of energy states near Dirac point and small screening length of graphene. [30,31] Although the tunable barrier height is the key to the physical picture of graphene/semiconductor Schottky diode, and structures with thin metal, ferroelectric polymer and ionic liquid as gating layer have been employed in graphene based electronic and optoelectronic devices [32][33][34][35][36][37][38][39][40], its applications in solar cell has not been explored systemically and the performance needs to further improved. Recently, Vazquez-Mena et al reported thin Au layer gated graphene/zinc phosphide solar cell with power conversion efficiency (PCE) of 1.9%, which is still low considering the relatively large band gap of zinc phosphide of 1.5 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Vazquez-Mena et al reported thin Au layer gated graphene/zinc phosphide solar cell with power conversion efficiency (PCE) of 1.9%, which is still low considering the relatively large band gap of zinc phosphide of 1.5 eV. [32] We have achieved PCE of 5.6% in graphene/InP heterostructure solar cell through tuning the Fermi level of graphene by gating effect [41]. The state of art PCE of graphene/semiconductor Schottky diode is 15.6% as achieved in graphene/Si system.…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2015, Royal Society of Chemistry. d) Reproduced with permission 81. Copyright 2014, American Chemical Society.…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%
“…Zettl et al presented a new type of field‐effect SC utilizing graphene and zinc phosphide (Zn 3 P 2 ) to form a tunable junction barrier thin‐film light absorber 81. To control the junction barrier between the graphene and a semiconductor, the Fermi level tuning of graphene is the key point.…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%
“…Meanwhile, several fabrication techniques have been adopted to prepare high performance thin film solar cells by using abundant materials. The absorber layer for the thin film solar cells can be prepared by various methods like sputtering, evaporation, electrodeposition, sol gel techniques, and spray pyrolysis [1][2][3][4][5][6][7][8][9][10][11], using abundant materials such as kesterite Cu 2 ZnSnS 4 (CZTS) [2], Cu 2 SnS 3 [12], Cu 2 S [13], SnS [14], Zn 3 P 2 [15], and hybrid perovskite CH 3 NH 3 PbI 3 [16][17][18]. In particular, the sputtering deposition technique has the advantages of easy control and tuning of the material composition of the film.…”
Section: Introductionmentioning
confidence: 99%